Adjuvant Endocrine Therapy in Premenopausal Breast Cancer: 12-Year Results From SOFT. Issue 7 (1st March 2023) - Francis, Prudence A.; Fleming, Gini F.; Láng, István; Ciruelos, Eva M.; Bonnefoi, Hervé R.; Bellet, Meritxell; Bernardo, Antonio; Climent, Miguel A.; Martino, Silvana; Bermejo, Begoña; Burstein, Harold J.; Davidson, Nancy E.; et al.
Abstract : Clinical trials frequently include multiple end points that mature at different times. The initial report, typically based on the primary end point, may be published when key planned co-primary or secondary analyses are not yet available. Clinical Trial Updates provide an opportunity to disseminate additional results from studies, published in JCO or elsewhere, for which the primary end point has already been reported. The Suppression of Ovarian Function Trial (SOFT; ClinicalTrials.gov identifier: NCT00066690 ) randomly assigned premenopausal women with hormone receptor–positive breast cancer to 5 years of adjuvant tamoxifen, tamoxifen plus ovarian function suppression (OFS), or exemestane plus OFS. The primary analysis compared disease-free survival (DFS) between tamoxifen plus OFS versus tamoxifen alone; exemestane plus OFS versus tamoxifen was a secondary objective. After 8 years, SOFT reported a significant reduction in recurrence and improved overall survival (OS) with adjuvant tamoxifen plus OFS versus tamoxifen alone. Here, we report outcomes after median follow-up of 12 years. DFS remained significantly improved with tamoxifen plus OFS versus tamoxifen (hazard ratio, 0.82; 95% CI, 0.69 to 0.98) with a 12-year DFS of 71.9% with tamoxifen, 76.1% with tamoxifen plus OFS, and 79.0% with exemestane plus OFS. OS was improved with tamoxifen plus OFS versus tamoxifen (hazard ratio, 0.78; 95% CI, 0.60 to 1.01) and was 86.8% with tamoxifen, 89.0% with tamoxifen plus OFS, and 89.4% with exemestane plus OFS at 12 years. Among those who received prior chemotherapy for human epidermal growth factor receptor-2–negative tumors, OS was 78.8% with tamoxifen, 81.1% with tamoxifen plus OFS, and 84.4% with exemestane plus OFS. In conclusion, after 12 years, there remains a benefit from including OFS in adjuvant endocrine therapy, with an absolute improvement in OS more apparent with higher baseline risk of recurrence.